Body Dissatisfaction, Distorted Body Image and Disordered Eating Behaviors in University Students: An Analysis from 2017–2022 - Jiménez-Limas, Karime; Miranda-Barrera, Verónica Anayansi; Muñoz-Díaz, Karla Fernanda; Novales-Huidobro, Samantha Ruth; Chico-Barba, Gabriela (International journal of environmental research and public health, 2022)
University students, as young adults, are at risk for Body Dissatisfaction (BD) and Distorted Body Image (DBI), which are related to Disordered Eating Behaviors (DEBs). This study aimed to assess changes in the prevalence of these three conditions over six years; and the associations between them. Data was collected through an annual online survey from 2017 to 2022 at a private university in Mexico City. Students between 18–30 years old were invited to participate. Body image-related variables were assessed by the Stunkard’s Silhouettes and Body Mass Index, by self-reported height and weight. Disordered Eating Behaviors were measured by the Brief Disordered Eating Behaviors Questionnaire. A median of 250 students participated per year, with a median age of 21 years old. The prevalence was 63.5–71.7% for BD, 40.4–49.1% for DBI, and 25–38.3% for DEBs. DEBs and BD showed associations during the whole period (OR from 3.6 to 15.9, p ≤ 0.001); as well as DBI with DEBs (OR from 1.9 to 3.3, p < 0.05). Alterations in Body Image and eating behaviors are common conditions, mainly in women and in the young population. Therefore, it is important to promote screening for these conditions, as they usually remain undiagnosed, their prevalence is increasing worldwide, and their impact on physical and mental health has already been acknowledged.